Diagnostical value of arthroscopy of significance knee chronic monosynovitis of unknown origin - V V Lyalina (Научно-практическая ревматология, 2003)
Objective. To estimate arthroscopy diagnostic significance in knee chronic monosynovitis (CMS) of unknown origin. Methods. 83 pts (41 female and 42 male) aged 20 to 72 years with CMS were examined. Duration of the diseases varied from 2 months to 12 years. Origin of synovitis was unknown. Diseased knee joint arthroscopy was performed with synovial biopsy and microscopic examination of synovial tissue samples. Results. Early or atypical forms of at least 12 diseases were identified as reasons for CMS. Most often CMS reasons were rheumatoid arthritis, osteoarthritis, microcrystalline arthropathy. Presumable and final diagnosis coincidence was noted in 18,3%. Some CMS causes were not considered before the examination. Arthroscopy allowed to identify Knee joint CMS origin in 96,5%. Conclusion. Arthroscopy is a valuable diagnostic method and should be included in plan of obligatory examination of pts with knee joint CMS of unknown origin.